Convoys of Social Relations: Cohort Similarities and Differences over 25 years - Antonucci, Toni C. (Psychol Aging, 2019)
Longer life expectancies and declining fertility rates suggest changes in connectedness among older adults. This study examines cohort patterns in the links between age and social relations by testing the Convoy Model of Social Relations among two adult cohorts in 1980 and 2005. We hypothesize that despite societal changes, connectedness remains fundamental in later life. The data are drawn from a regionally representative sample (N=543) aged 50 to 100 collected in 2005 and a nationally representative sample (N=718) aged 50 to 95 collected in 1980. We use Multi-Level-Modeling to update the preliminary examination of how network characteristics vary by age and emotional closeness (Antonucci & Akiyama, 1987a) with data collected 25 years later. Findings indicate that network size, gender composition and years known were similar in both cohorts. Changes are also evident. In 2005, network members were older, had more frequent contact and lived closer to their network members than in 1980. There was one cohort difference in network composition, the proportion of other family was smaller in 2005 compared to 1980. Finally, cohorts differed in the effects of age (e.g. on contact frequency), closeness (e.g. on network size) and age x closeness interactions (e.g. on sibling composition). In sum, overall patterns of network structure and composition are largely similar in the two cohorts. The effects of age and emotional closeness were largely consistent over 25 years. Although caution is warranted, these findings provide continued support for the importance of close relations in later life across historical periods.